Nethouse Technology for Potato Seed Production: Empowering Farmers in Sedaeng Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This Community Partnership Program (PKM) aimed to enhance the productivity, independence, and technical capabilities of the Laksmana Agrobisnis Farmer Group in Sedaeng Village, Tosari, Bromo, through the application of net house technology for potato seedling propagation. Before the intervention, seedling production was conducted manually on household terraces, yielding only around 2,500 G0 seedlings per season with inconsistent quality, high susceptibility to disease, and elevated production costs. The introduction of a 6×8 m permanent nethouse, accompanied by structured technical training and mentoring, resulted in a tenfold increase in productivity, producing approximately 25,000 G0 and 10,000 G1 seedlings per cycle. Production costs decreased substantially from Rp 77,500,000 to Rp 8,550,000, generating an estimated cost efficiency and measurable profits for the group. The program was implemented over eight months using a participatory and applicative approach that combined counseling, demonstration, and mentoring. Farmers developed practical competencies in propagation techniques, nutrient management, and pest control, enabling independent and sustainable seed production. Land utilization efficiency also improved, with 10,000 m² of farmland previously underutilized now fully cultivated with uniform, high-quality seedlings. Beyond technical achievements, the program fostered gender-inclusive participation, strengthened group collaboration, and enhanced the community’s ability to adopt innovation in local agribusiness practices. Overall, this PKM program demonstrates that the adoption of nethouse technology is both technically feasible and socio-economically empowering. It improves production efficiency, reduces dependency on external seed sources, and fosters long-term sustainability among highland potato farmers. The successful implementation in Sedaeng Village serves as a replicable empowerment model for other potato-producing regions in East Java and similar highland communities across Indonesia.